2020
DOI: 10.1126/scitranslmed.aax3799
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 and senescent cells regulate the foreign body response to synthetic material implants in mice and humans

Abstract: Medical devices and implants made of synthetic materials can induce an immune-mediated process when implanted in the body called the foreign body response, which results in formation of a fibrous capsule around the implant. To explore the immune and stromal connections underpinning the foreign body response, we analyzed fibrotic capsules surrounding surgically excised human breast implants from 12 individuals. We found increased numbers of interleukin 17 (IL17)–producing γδ+ T cells and CD4+ T helper 17 (TH17)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 69 publications
2
138
0
1
Order By: Relevance
“…Notably, the senolytic action of ABT-263 appears to depend on inhibition of BCL-X L and/or BCL-W, while BCL-2 inhibition is dispensable [84,86]. Similar to D+Q, ABT-263 was successful in eliminating senescent cell populations in several disease models including aging-associated bone loss [87], radiation-induced lung fibrosis [88], lung emphysema [89], uterine leiomyoma [90], tau-dependent neurodegenerative disease [91], radiation-induced neurodegeneration [92], myocardial infarction (including ischemia-reperfusion injury) [93,94], heart failure [95], pulmonary hypertension [96], insulin resistance [97], osteoarthritis [98,99], synthetic implant-mediated fibrosis [100], and Duchenne muscular dystrophy [101]. ABT-263 is currently a cornerstone in preclinical studies of senolysis and remains a promising drug for use against both liquid and solid tumors [102][103][104].…”
Section: Senolytic Therapies: Have We Hit Gold or Pyrite? 21 Establmentioning
confidence: 99%
“…Notably, the senolytic action of ABT-263 appears to depend on inhibition of BCL-X L and/or BCL-W, while BCL-2 inhibition is dispensable [84,86]. Similar to D+Q, ABT-263 was successful in eliminating senescent cell populations in several disease models including aging-associated bone loss [87], radiation-induced lung fibrosis [88], lung emphysema [89], uterine leiomyoma [90], tau-dependent neurodegenerative disease [91], radiation-induced neurodegeneration [92], myocardial infarction (including ischemia-reperfusion injury) [93,94], heart failure [95], pulmonary hypertension [96], insulin resistance [97], osteoarthritis [98,99], synthetic implant-mediated fibrosis [100], and Duchenne muscular dystrophy [101]. ABT-263 is currently a cornerstone in preclinical studies of senolysis and remains a promising drug for use against both liquid and solid tumors [102][103][104].…”
Section: Senolytic Therapies: Have We Hit Gold or Pyrite? 21 Establmentioning
confidence: 99%
“…IL-17 secreted by group 3 innate lymphoid cells, γδ T cells and CD4+ adaptive T cells (Th17) can modulate extracellular matrix organization and fibrosis. (16,17) Previous studies usually focused on certain types of immune cells, like macrophages, and explored their roles in the host response. However, the immune response is concomitantly regulated by various immune cells, whose phenotype and function are dictated by external and internal signals.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, in type 2 immune response, T helper 2 (Th2) cells produce cytokines like IL-4 and IL-13, which regulate the polarization of macrophages towards an anti-inflammatory M2 activation (9, 10). More recently, a type 17 immune response was reported to promote chronic fibrosis in tissue around implants (11, 12). In summary, previous studies usually focused on certain types of immune cells, like macrophages, and explored their roles in the host response.…”
Section: Introductionmentioning
confidence: 99%
“…Previous preclinical studies showed that a proregenerative macrophage phenotype is required for repair using biological ECM scaffolds, and that a local TH2 response is required for promoting the pro-regenerative macrophage phenotype that develops in response to biological scaffolds 11 . This type 2 mediated response contrasts the macrophage and T cell phenotypes that develop around synthetic implants which includes inflammatory macrophages fusing to form foreign body giant cells and the more recently defined TH17 T cell and senescent cell phenotypes 28 . The proregenerative or "M2" macrophage response to biological scaffolds was validated clinically in biopsies from large muscle defects treated with small intestinal submucosa-derived ECM 29…”
Section: Discussionmentioning
confidence: 93%